Cracks in the Continuum: A Critical Analysis of Least Restrictive Environment for Students with Significant Support Needs. Issue 5 (May 2020) - Mccabe, Katie M.; Ruppar, Andrea; Kurth, Jennifer A.; Mcqueston, Jessica A.; Johnston, Russell; Toews, Samantha Gross
Background/Context: Federal laws require equitable access to education for students with disabilities through educational placement in the least restrictive environment (LRE). However, research has determined students with significant support needs (SSN) are overrepresented in segregated educational placements. Focus of Study: This study explores justifications of LRE placement decisions for students with SSN through a critical qualitative analysis. We evaluated how individualized education program (IEP) teams interpret LRE and justify placement decisions for students with SSN. Additionally, we sought to understand how the interpretation of LRE permits or restricts access to general education for students with SSN. Population: Students with SSN are those who require support across multiple domains and often have disabilities in the categories of autism, intellectual disability, multiple disabilities, and deaf-blindness. Research Design: We used a qualitative methodology situated in a critical geography framework. Data were derived from the LRE statements found in IEPs of students with SSN. Each statement included in this study was used to identify the three power relationship spaces derived from critical geography theory: utopia, dystopia, and heterotopia. Findings: Three types of placement decisions were identified. Students with SSN were most often offered conditional placements and less frequently closed or open placements. Rationales for LRE decisions revealed barriers to accessing general education contexts related to hidden power dynamics, attempts to maintain social norms, and the use of ambiguous terminology. Data analysis also revealed that LRE justifications generate special education heterotopias that create illusive access to the general education context and content for students with SSN. Conclusions/Recommendations: The application of critical theory assists in understanding the continued overrepresentation of students with SSN in placements that limit access to general education. Findings from this study suggest the discontinuation of the continuum of special education placements to dismantle the inequitable structures of special education for students with SSN.